Formation of professionaly significant qualities of students by means of foreign language - Natalia V. Ageyenko; Tatiana A. Fedorova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article deals with the problem of training qualified specialists in the process of learning foreign languages. It is noted, in the present conditions of development of society it is necessary to develop spiritually rich personality possessing creativity,high professional culture, morality.The study of linguistic personality and especially his verbal behavior in a foreign language with the complex of methods of different sciences is the up-to-date task of scientific knowledge. the concept of a three-tier structure of linguistic personality, it is defined as the correlation between the three types of communication needs as well as the three sides of the communication process- communicative, interactive and perceptive, reflecting the nature of activities of a journalist and is closely related to its functions. The article suggests the algorithmformation of professionally significant qualities of students in different activities.